Evaluation of severe acute maternal morbidity and mortality at a tertiary referral center of Uttarakhand, India - Verma, Lipi; Nautiyal, Ruchira; Aggarwal, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal mortality is an area of concern for the Governments across the globe. India is signatory to millennium declaration and is committed to achieving the target of millennium development goals by reducing MMR to 100. Known obstacles to reducing the MMR in developing countries, include lack of material and human resources, as well as difficulties in accessing services due to financial, geographical, and cultural limitations. Methods: It was a descriptive cross-sectional study conducted at a tertiary care centre in Uttarakhand for a period of one year. WHO’s near-miss approach was implemented for evaluation of severe maternal outcomes and to assess the quality of maternal health care. Results: During the period of this study there were 2243 total antenatal admissions, 1675 deliveries, 1591 live births and 59 near miss cases. Prevalence of SAMM in the present study is 3.52%. Out of every 9-10 women who survived a life-threatening condition 1 died. Mortality Index is 10.17%. Maternal mortality ratio is 377.12 per 1 lakh live births. A total of 43 patients with potentially life-threatening conditions were admitted in ICU out of which 26 were near miss cases. The leading cause of near miss in this tertiary health facility is obstetric haemorrhage (45.8%). Conclusions: Prompt identification of complications and timed intervention remains the key determinant in making mothers survive a life-threatening complication.